Penilaian Green Building Gedung Sarana Square Jakarta Selatan Menggunakan Greenship Versi 1.2 - Marson Maizi; Yosi Valentina Simorangkir (Musamus Journal of Architecture, 2022)
Green Building planning basis refers to GBCI certification. This article aims to obtain an assessment index of the application of the Green Building concept at the Sarana Square Building north of Jakarta. The research method uses the Greenship index scale for new buildings version 1.2, collecting data by means of observation, interviews & data from the planner, namely plan drawings, BoQ, RKS, Design Recognition (DR) & the implementation process carried out when the project is in design finalization planning & implementation process. The results of the index scale assessment show that the building gets a total index of 37 points, a percentage of 48.05%, with a silver/silver predicate if people with disabilities, renewable energy, waste management, water conservation, than the building gets a total index of 48 points with a predicate of 62.34% with predicate gold Gbci, green building, sarana square,index scale.